How Antitrust Enforcement Can Spur Innovation: Bell Labs and the 1956 Consent - Martin Watzinger; Thomas Fackler; Markus Nagler; Monika Schnitzer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We study the 1956 consent decree against the Bell System to investigate whether patents held by a dominant firm are harmful for innovation and if so, whether compulsory licensing can provide an effective remedy. The consent decree settled an antitrust lawsuit that charged Bell with having foreclosed the market for telecommunications equipment. The terms of the decree allowed Bell to remain a vertically integrated monopolist in the telecommunications industry, but as a remedy, Bell had to license all its existing patents royalty-free. Thus, the path-breaking technologies developed by the Bell Laboratories became freely available to all US companies. We show that in the first five years compulsory licensing increased follow-on innovation building on Bell patents by 17%. This effect is driven mainly by young and small companies. Yet, innovation increased only outside the telecommunications equipment industry. The lack of a positive innovation effect in the telecommunications industry suggests that market foreclosure impedes innovation and that compulsory licensing without structural remedies is ineffective in ending it. The increase of follow-on innovation by small and young companies is in line with the hypothesis that patents held by a dominant firm act as a barrier to entry for start-ups. We show that the removal of this barrier increased long-run U.S. innovation, corroborating historical accounts
Keywords: O30; O33; O34; K21; L40; 330